PENGUATAN LITERASI MATEMATIKA DALAM PERSPEKTIF MULTIPLE INTELLIGENCES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Ni`mah, Masrifatul; Alhusna, Elma; Hamzah, M. Ali Imron; Rahaju, Endah Budi; Wahyu, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the 2018 PISA results, Indonesian students' abilities in reading, mathematics and science are below the OCED average. The government's effort to deal with the reality about students is the implementation of the Independent Curriculum which uses the Pancasila student profile as character traits and competencies that students are expected to achieve based on the noble values ​​of Pancasila, one of which is the ability to think critically. A diversity of critical thinking abilities is often found in mathematics classes. This is because every individual has eight different intelligences in multiple intelligences. So it is necessary to strengthen mathematical literacy to support the government in its independent curriculum policy, where students are required to be able to think critically in learning, especially mathematics. This research uses descriptive qualitative research, with material on the properties of triangles and quadrilaterals taken during the implementation of PPL 2 at SMPN 8 Kediri.